2020
DOI: 10.1039/d0py01399d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of (E)-1,2-bis(3-cyanothiophene-2-yl)ethene-based polymeric semiconductors for unipolar n-channel field-effect transistors

Abstract: The exploration of unipolar n-channel semiconductors plays an important role in the advance of organic complementary inverters and complementary logic circuits. Based on the conventional donor–acceptor type conjugated copolymers, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Tetrahydrofuran (THF) was dried in accordance with standard processes. 4,9‐dibromo‐2,7‐bis(2‐decyltetradecyl)benzo[ lmn ][3,8]phenanthroline‐1,3,6,8(2 H ,7 H )‐tetraone (NDI‐C 10 C 12 ), [ 34 ] 5,5′‐bis(trimethylstannyl)‐[2,2′‐bithiophene]‐3,3′‐dicarbonitrile (BTCN‐Sn), [ 35 ] ( E )‐2,2′‐(ethene‐1,2‐diyl)bis(5‐(trimethylstannyl)thiophene‐3‐carbonitrile) (TVTCN‐Sn), [ 29 ] and ( E )‐1,2‐bis(3‐bromoselenophen‐2‐yl)ethene (SVS‐Br) [ 31 ] were synthesized according to the procedures previously reported. To elevate the molecular weights of polymers, all the trimethyltin reagents were recrystallized before polymerization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahydrofuran (THF) was dried in accordance with standard processes. 4,9‐dibromo‐2,7‐bis(2‐decyltetradecyl)benzo[ lmn ][3,8]phenanthroline‐1,3,6,8(2 H ,7 H )‐tetraone (NDI‐C 10 C 12 ), [ 34 ] 5,5′‐bis(trimethylstannyl)‐[2,2′‐bithiophene]‐3,3′‐dicarbonitrile (BTCN‐Sn), [ 35 ] ( E )‐2,2′‐(ethene‐1,2‐diyl)bis(5‐(trimethylstannyl)thiophene‐3‐carbonitrile) (TVTCN‐Sn), [ 29 ] and ( E )‐1,2‐bis(3‐bromoselenophen‐2‐yl)ethene (SVS‐Br) [ 31 ] were synthesized according to the procedures previously reported. To elevate the molecular weights of polymers, all the trimethyltin reagents were recrystallized before polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the electron‐withdrawing units of sp 2 ‐hybridized nitrogen atoms and fluorine atoms, the introduction of cyano groups is also a feasible method in modulation of majority of carrier transport type as demonstrated by Hwang et al [ 28 ] Recently, our group reported a series of unipolar n‐type conjugated polymers based on the cyano‐substituted ( E )‐1,2‐di(thiophen‐2‐yl)ethene, i.e., ( E )‐1,2‐bis(3‐cyanothiophene‐2‐yl)ethene. [ 29 ] Guo et al also synthesized n‐type polymeric semiconductors by adopting cyano‐functionalized strategy. [ 30 ] These results demonstrate that n‐type semiconductors would be achieved via this method.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they synthesized two copolymers (P32a and P32b) of 2CNTVT and AIID or FIID. [ 122 ] The CN groups significantly lowered the HOMO/LUMO energy levels of P32a and P32b to −6.15/−3.81 and −6.12/−3.82 eV, respectively. TGBC OFETs based on P32a and P32b exhibited unipolar n‐type characteristics with μ e s of 1.58 and 0.66 cm 2 V −1 s −1 , respectively.…”
Section: Improving the Electron Transport Of D–a‐type Sps Via Amsmentioning
confidence: 99%
“…According to the available data, the most studied polymeric isoindigos are dithienyl derivatives, in which two thiophene fragments can be linked to each other [74][75][76][77][78][79][80][81][82][83][84][85][86] or be separated by spacers of different structures [87][88][89][90][91]. Structures containing a 2,2'-dithienyl fragment can be divided into three types: 1) not containing substituents in the benzo and thienyl fragments; 2) containing fluorine atoms in the thienyl fragment; and 3) containing fluorine atoms in positions 7,7' and in thienyl fragments (Scheme 24).…”
Section: Isoindigo As the Basis For Organic Field-effect Transistors (Ofet)mentioning
confidence: 99%
“…Liu et al explain this effect by an improvement in the hole-type conductivity and a tight and even packing of the composite in a thin film [ 80 ]. At the same time, selenophene analogs generally show lower values of mobility [ 90 ]. The introduction of fluorine atoms into the dithienyl fragment (see compound 46 ), while varying the symmetry of substitution of the 1,1' positions in isoindigo, did not lead to an improvement in the OFET efficiency (maximum μ h = 1.08 cm 2 ⋅V −1 ⋅s −1 ).…”
Section: Reviewmentioning
confidence: 99%